Cell Factory Engineering of Undomesticated Bacillus Strains Using a Modified Integrative and Conjugative Element for Efficient Plasmid Delivery - Jeong, Da-Eun; Kim, Man Su; Kim, Ha-Rim; Choi, Soo-Keun (Frontiers in Microbiology, 2022)
A large number of Bacillus strains have been isolated from various environments and many of them have great potential as cell factories. However, they have been rarely developed as cell factories due to their poor transformation efficiency. In this study, we developed a highly efficient plasmid delivery system for undomesticated Bacillus strains using a modified integrative and conjugative element (MICE), which was designed to be activated by an inducer, prevent self-transfer, and deliver desired plasmids to the recipient cells. The MICE system was demonstrated to successfully introduce a gfp-containing plasmid into all 41 undomesticated Bacillus subtilis strains tested and eight other Bacillus species. The MICE was used to deliver a cytosine base editor (CBE)-based multiplex genome-editing tool for the cell factory engineering of the Bacillus species. The introduced CBE enabled one-step inactivation of the major extracellular protease genes of the tested strains. The engineered strains were used as hosts for heterologous expression of nattokinase, which resulted in various enzyme expression levels. The results suggested that the MICE and CBE systems can be powerful tools for genetic engineering of undomesticated Bacillus strains, and greatly contribute to the expansion of the Bacillus cell factory.